2016
DOI: 10.1111/jfpe.12478
|View full text |Cite
|
Sign up to set email alerts
|

Use of pineapple waste for single cell protein (SCP) production and the effect of substrate concentration on the yield

Abstract: Single cell protein (SCP) is used as a protein supplement in animal feed and protein rich foods for humans. In this study, extracts of pineapple waste were used as substrate for SCP production using Saccharomyces cerevisiae sp. (Baker or brewing yeast). The study also focused on the effect of the pineapple substrate concentration on the yield of SCP. Pineapple waste were collected from food processing companies in Kumasi and processed into pineapple juice extracts. The residual soluble sugars in the extract we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 6 publications
3
29
0
Order By: Relevance
“…The protein content of FPP and FPC was low, while SI had a considerably high protein and lignosellulosic content (Table 2). Therefore, SIS favours SFS since N 2 is a necessary element in microbial metabolism during cell growth (Mensah and Twumasi, 2017). Similar protein contents in SIS (59%) have been reported by Wang et al (2018).…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…The protein content of FPP and FPC was low, while SI had a considerably high protein and lignosellulosic content (Table 2). Therefore, SIS favours SFS since N 2 is a necessary element in microbial metabolism during cell growth (Mensah and Twumasi, 2017). Similar protein contents in SIS (59%) have been reported by Wang et al (2018).…”
Section: Resultssupporting
confidence: 77%
“…Among the evaluated residues, the pineapple peel is outstanding due to the high concentration of reducing sugars (97 g L À1 ) obtained through the application of acid hydrolysis as a pre-treatment (Vega-Castro et al 2016). In addition, pineapple waste has been used to produce cellular protein (Mensah and Twumasi, 2017). Pineapple is part of the bromeliad family, and, in 2017, world production was 27 million tons with a harvested area of 1 million ha.…”
Section: Introductionmentioning
confidence: 99%
“…In all isolates the colony forming units were uncountable at zero dilution. This result in conformity with Adams et al, (2014), Kwiatkowski et al, (2015), Mensah and Twumasi (2016), Hendry et al, (2014), even they could find 40 plates out of 1440 were having uncountable colonies due to spreading of the colonies. It was observed that the plates were having uncountable colonies at zero dilution because of more number of colonies and due to spreading.…”
Section: Isolation and Characterization Of Six Bacterial Isolatessupporting
confidence: 91%
“…The use of agroindustrial residues of pineapple as a supplement usually involves the use of microorganisms for protein enrichment. For example, Mensah and Twumasi (2017) used pineapple residues as a substrate for production of Single Cell Protein (SCP) with yeast Saccharomyces cerevisiae as inoculum. According to its results, it was concluded that residues from the food processing industry serve as good substrates for SCP production, which presents high benefit.…”
Section: Protein Supplementmentioning
confidence: 99%